OPTIMIZATION OF CONTROLLED RELEASE UREA PRODUCTION USING MODIFIED BIOPOLYMER AS COATING MATERIAL IN FLUIDIZED BED - AZEEM, BABAR (2017)
Pristine urea is lost due to ammonia volatilization, leaching, and surface runoff. Synthetic polymers coated controlled release urea (CRU) is used as an abatement strategy but it offers soil pollution due to non-biodegradability and toxicity of the polymers. Coating heterogeneities on the surface of urea granules cause poor release characteristics of CRU